2021
DOI: 10.3390/nano11102591
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermoelectric Performance of Polycrystalline Si0.8Ge0.2 Alloys through the Addition of Nanoscale Porosity

Abstract: Engineering materials to include nanoscale porosity or other nanoscale structures has become a well-established strategy for enhancing the thermoelectric performance of dielectrics. However, the approach is only considered beneficial for materials where the intrinsic phonon mean-free path is much longer than that of the charge carriers. As such, the approach would not be expected to provide significant performance gains in polycrystalline semiconducting alloys, such as SixGe1-x, where mass disorder and grains … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Both indium chalcogenides and metal halides are ductile in nature, whereas SnSe is brittle as observed from its values of ξ. Calculated sound velocities of the heat carrying acoustic branch of phonon, Debye temperature, Young’s modulus, and shear modulus are significantly lower in In 4 (Te/Se) 3 than those of the established TE materials, such as Si 0.8 Ge 0.2 (∼5572 m s –1 ) and Mg 2 (Si/Ge/Sn) (∼7300, 6400, 4300 m s –1 ), and comparable to the other state-of-the-art TE materials, such as CuBiI 4 (1487 m s –1 ), Cs 3 Bi 2 I 9 (1297 m s –1 ), Cu 2 Se (1581 m s –1 ), and Bi 2 Te 3 (1761 m s –1 ) . Low sound velocity corresponds to weak In–Te interatomic bonding and eventually leads to low κ L as κ L ∝ v av 3 .…”
Section: Resultsmentioning
confidence: 57%
“…Both indium chalcogenides and metal halides are ductile in nature, whereas SnSe is brittle as observed from its values of ξ. Calculated sound velocities of the heat carrying acoustic branch of phonon, Debye temperature, Young’s modulus, and shear modulus are significantly lower in In 4 (Te/Se) 3 than those of the established TE materials, such as Si 0.8 Ge 0.2 (∼5572 m s –1 ) and Mg 2 (Si/Ge/Sn) (∼7300, 6400, 4300 m s –1 ), and comparable to the other state-of-the-art TE materials, such as CuBiI 4 (1487 m s –1 ), Cs 3 Bi 2 I 9 (1297 m s –1 ), Cu 2 Se (1581 m s –1 ), and Bi 2 Te 3 (1761 m s –1 ) . Low sound velocity corresponds to weak In–Te interatomic bonding and eventually leads to low κ L as κ L ∝ v av 3 .…”
Section: Resultsmentioning
confidence: 57%
“…Based on the Vienna Ab initio Simulation Package (VASP), generalized gradient approximation of Perdew–Burke–Ernzerhof functions were employed to carry out density functional theory (DFT) calculations. , To describe the interactions between ion cores and valence electrons, the projector augmented wave method was adopted, and the Kohn–Sham equations were expanded in a plane wave basis set with a cutoff energy of 400 eV. Brillouin zone sampling was performed by using a Monkhorst–Pack k -point grid . According to the XRD data, the (111) surface was chosen for investigating the activity of Pt metal and AuPt alloy catalysts.…”
Section: Methodsmentioning
confidence: 99%
“…The ratio of Si to Ge was studied for optimal composition to maximize the scattering of acoustic phonons, and it was found that a 20% substitution of Ge exhibited a significant decrease in thermal conductivity to ~9 W cm −1 K, and a further addition of Ge contributed insignificantly [138]. Additionally, Ge is about 100 times more costly as compared with Si [139]. Therefore, minimizing the required amount for substitution would be financially beneficial.…”
Section: Silicon Germaniummentioning
confidence: 99%